Sejarah Perkembangan Bahasa Indonesia - Ade Suryani Nasution; Anis Syafa Wani; Edi Syahputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Indonesia is a country that is rich in various languages, especially Malay. The Malay language was the beginning of the formation of the Indonesian language which was ratified at the youth oath event. Seeing this, it is clear that Malay is the first language of the formation of Indonesian as the state language and national language. The purpose of writing this journal is to find out the history and position of the Indonesian language in Indonesia. The research method used is descriptive qualitative research method with the type of research library research. The results showed that the formation of the Indonesian language originated from the Malay language which was originally used as the language of inter-ethnic communication. The position of the Indonesian language is inseparable from 4 functions, namely as a language of communication, a unifying language, the language of the state and the national language.